Pengaruh E-Payment Dan Literasi Digital Terhadap Penjualan UMKM Di Kota Mataram (Studi Kasus Coffeeshop) - Serena, Baiq Serena Diva Sabatini; Animah; Priyambodo, Victoria Kusumaningtyas (Jurnal Riset Mahasiswa Akuntansi, 2025)
This study aims to analyze the effect of e-payment and digital literacy on sales in MSMEs, especially coffeeshops. The rapid development of information and communication technology, especially in the digital payment sector, encourages MSMEs to adapt in order to remain competitive. By integrating an electronic payment system (e-payment), MSME coffeeshop actors can facilitate transactions and increase operational efficiency. On the other hand, adequate digital literacy in business actors also plays an important role in utilizing technology optimally, both in product marketing and business management. This research method uses a quantitative approach by distributing questionnaires to coffeeshop owners, managers and employees as respondents. Data were collected through questionnaires and analyzed using multiple linear regression. The results of the study indicate that both e-payment and digital literacy have a significant influence on increasing sales of MSME coffeeshops. E-payment provides convenience for consumers and speeds up transactions, while digital literacy allows managers to be more effective in using online platforms for marketing and interaction with consumers. This study suggests that MSME coffeeshops improve their understanding and use of digital technology to maximize their sales potential.